Desenvolvimento de um modelo preditivo para identificação de perda de estabilidade e ocorrência de proteólise em leite UAT - Mariana Coelly Modesto Santos (2015)
The aim of this work was to develop a predictive model for identifying loss of stability and sedimentation in UHT milk by determining the enzymatic activity of aminopeptidasis in milk by spectrophotometry. Were analyzed samples of raw milk, pasteurized and UHT after filling for 6 months in Southern Brazil. Acidity, freezing point, fat, total solids, nonfat solids and density were analyzed in raw and pasteurized milk. Of raw milk samples were also subjected to psychrotrophic count analysis and aminopeptidasis activity and UAT samples stored milk were analyzed for degree of proteolysis through sensory analysis and aminopeptidasis activity. Sensory changes were observed in smaller storage time for samples of raw milk originated with psychrotrophic count above 107 CFU ml -1. There was no correlation between aminopeptidasis activity and proteolysis and was also no significant correlation between physicochemical parameters and the occurrence of proteolysis in stored milk. The model was unable to predict loss of stability and occurrence of proteolysis in UHT milk.